Case 3833: Hyla prasina Burmeister, 1856 (currently Boana prasina; Amphibia, Anura, Hylidae): proposed precedence over Hyla quoyi Bory de Saint-Vincent, 1828 - Costa, Henrique C; Santana, Diego J; Kolenc, Francisco; Baldo, Diego; Caramaschi, Ulisses; Dubois, Alain; Ohler, Annemarie (Bulletin of Zoological Nomenclature)
Noticed in BZN 77: 113 on 30 December 2020.